The Influence of Religious Beliefs and Religious Practices on Social Cohesion in Modern Society in Indonesia - Judijanto, Loso; Siminto, Siminto; Rahman, Rahman (The Eastasouth Journal of Social Science and Humanities, 2024)
This research investigates the influence of religious beliefs and practices on social cohesion in modern Indonesian societies through a quantitative analysis. A sample of 175 respondents representing diverse religious communities participated in the study. The survey instrument utilized Likert scales to measure religious beliefs, practices, and various dimensions of social cohesion. Structural Equation Modeling (SEM) with Partial Least Squares (PLS) analysis was employed to analyze the data. The results revealed significant positive relationships between religious beliefs, practices, and social cohesion. Specifically, stronger religious beliefs were associated with higher levels of social cohesion, while active engagement in religious practices contributed to increased social cohesion. The findings highlight the integral role of religion in fostering community resilience and well-being. These insights have implications for policymakers, community leaders, and scholars seeking to promote social cohesion and interfaith harmony in diverse societies.